RANCANG BANGUN DAN IMPLIKASI EPISTIMOLOGIS KEILMUAN PESANTREN DI INDONESIA - Made Saihu (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This research proves that nalar Bayani, Irfani, and Burhani as a mapping of the Islamic scientific framework should be powerful enough to be used as an analysis knife for pesantren science as manifested in the yellow books taught in various Islamic boarding schools in Indonesia. With this scientific mapping, it is evident that most of the yellow books taught in various islamic boarding schools are dominated by Bayani reason or in other terms al-'Aqliyat al-Syar'iyyah which is widely applied in the field of kalam and fiqh. Meanwhile, in the field of morals, many are colored by Irfani's reasoning, although there are temporary moral books that use Bayani reason such as the book of Ta'limal-Muta'allim, and there is also a book that combines the three forms of reasoning with its emphasis on Irfani's reasoning, namely the book of Ihya' Ulum al-Din.